Glucocorticoids in myocarditis therapy after COVID-19. (14th October 2021) - Kovalenko, V; Nesukay, E; Cherniuk, S; Kirichenko, R; Kozliuk, A; Titova, N; Titov, E; Giresh, J
Abstract: : The aim of the study - to evaluate the efficacy of glucocorticoids (GC) in patients with acute myocarditis (AM) after COVID-19 infection. Material and methods: We included 60 pts with severe AM and heart failure (HF) with reduced (<40%) left ventricular (LV) ejection fraction (EF) who had COVID-19 infection 1–2 months before the enrollment. According to the results of cardiac magnetic resonance (CMR) included pts had ≥2 Lake Louise criteria for myocarditis. All pts on the background of HF therapy (β-blockers, ACE-inhibitors, MRA antagonists, diuretics) were prescribed GC: 0.25 mg/kg per day methylprednisolone for 3 months, followed by a gradual dose reduction of 1–2 mg per week until complete discontinuation after 6 months. Evaluation before the start of GC therapy and after 6 months included CMR, 2D- and speckle-tracking echocardiography. Results: After 6 months according to the results of CMR the number of LV segments with inflammatory lesions decreased to (3, 58±0, 42) from (6, 32±0, 77) segments in average (p=0, 001). This was followed by improvement of LV systolic function: increase of LV EF in average to (43, 5±2, 6) from (32, 2±2, 4) % (p=0, 003), longitudinal global systolic strain (LGSS) absolute value to (11, 3±1, 1) from (7, 9±0, 5) % (p=0, 012) and circumferential global systolic strain (CGSS) to (12, 1±1, 0) from (8, 9±0, 6) % (p=0, 023). Also we observed LV volume reduction: decrease of LV end-diastolic (from 118, 9±8, 6 to 95, 3±7, 2 ml/m 2, p=0, 033) and LV end-systolic (from 80, 1±5, 1 to 59, 1±4, 4 ml/m 2, p=0, 027) volume indexes. Wherein in 24 of 60 pts (41, 6%) on the background of significant decrease in the number of LV segments with inflammatory lesions (to 1, 34±0, 21 from 6, 12±0, 73 segments, p=0, 0001) after 6 months we observed the recovery of LV EF ≥50%, followed by an improvement of LGSS and CGSS on 42, 1 and 39, 4% respectively (p=0, 001). According to multivariate regression analysis, predictors of LV EF recovery (≥50%) after 6 months of GC treatment were established: presence of inflammatory lesions in ≤5, 0 LV segments, values of LGSS and CGSS ≥9.0% and ≥9.5% respectively before the start of GC. Conclusions: The use of GC in pts with severe AM after COVID-19 was followed by the decrease of LV segments number affected by inflammation, improvement of LV systolic function and reduction of LV volume indexes. In 41, 6% of pts GC therapy was associated with LV EF recovery after 6 months and predictors of its effectiveness were found: presence of inflammatory lesions in ≤5, 0 LV segments, values of LGSS and CGSS ≥9.0% and ≥9.5% respectively before the start of GC. Funding Acknowledgement: Type of funding sources: None.